Magnetic Field Effects on CaCO3 Precipitation Process in Hard Water - Saksono, Nelson; Bismo, Setijo; Krisanti, Elsa; Manaf, Azwar; Widaningrum, Roekmijati (UI Scholars Hub, 2006)
Magnetic Field Effects on CaCO3 Precipitation Process in Hard Water. Magnetic treatment is applied as physical water treatment for scale prevention especially CaCO3, from hard water in piping equipment by reducing its hardness. Na2CO3 and CaCl2 solution sample was used in to investigate the magnetic fields influence on the formation of particle of CaCO3. By changing the strength of magnetic fields, exposure time and concentration of samples solution, this study presents quantitative results of total scale deposit, total precipitated CaCO3 and morphology of the deposit. This research was run by comparing magnetically and non-magnetically treated samples. The results showed an increase of deposits formation rate and total number of precipitated CaCO3 of magnetically treated samples. The increase of concentration solution sample will also raised the deposit under magnetic field. Microscope images showed a greater number but smaller size of CaCO3 deposits form in magnetically treated samples, and aggregation during the processes. X-ray diffraction (XRD) analysis showed that magnetically samples were dominated by calcite. But, there was a significant decrease of calcite’s peak intensities from magnetized samples that indicated the decrease of the amount of calcite and an increase of total amorphous of deposits. This result showed that magnetization of hard water leaded to the decreasing of ion Ca2+ due to the increasing of total CaCO3 precipitation process.